2007
DOI: 10.1271/bbb.70069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by GC–MS of Vietnamese Citrus Species and Hybrids Based on the Isotope Ratio of Monoterpene Hydrocarbons

Abstract: The isotope ratio of monoterpene hydrocarbons was used to characterize the citrus essential oils from different species and hybrids. Citrus cold-pressed peel oils from Vietnam were analyzed for the composition and isotope ratio of monoterpene hydrocarbons by using gas chromatography-mass spectrometry. A profile of citrus essential oils on the basis of their isotope ratio values and levels of monoterpene hydrocarbons was developed for Vietnamese citrus. The molecular isotope ratios were lower than those calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Herein the retention time of b-pinene was found lower to the respective of myrcene. This result is in compliance with the study of Thao et al [ 16 ] using a similar DB5 column. Overall, when the natural product was profiled, more terpenes were detected compared to the blood samples.…”
Section: Discussionsupporting
confidence: 93%
“…Herein the retention time of b-pinene was found lower to the respective of myrcene. This result is in compliance with the study of Thao et al [ 16 ] using a similar DB5 column. Overall, when the natural product was profiled, more terpenes were detected compared to the blood samples.…”
Section: Discussionsupporting
confidence: 93%
“…The number of components, as shown in Figure 6 is listed in Table 4 provided with concentration data. Figure 8 Fragmentation mechanisms of limonene and terpinene yielding C7H9 fragment (Thao et al, 2007) The highest content of limonene obtained by this study is found to be 29.89 % (Table 4). Njoku and Evbuomwan ( et al, 2014) found a limonene content of 17.07 % in Nigerian lime peel applying the distillation method.…”
Section: Gc-ms Analysismentioning
confidence: 72%